Aprendizagem significativa e as variáveis chave em Ballester: proposta didática para abordar eletricidade no ensino fundamental - Paula, José de Arimatéia Monteiro de (2023)
The present study takes as a problem the need for Science teaching aimed at promoting meaningful learning of concepts, phenomena and their applications. To do so, it uses the Meaningful Learning Theory (TAS) in David Ausubel and the key variables announced by Antoni Ballester as a possibility to promote meaningful learning in the classroom. As key variables, Ballester (2018; 2002) infers a set of aspects that seek to bring a new organization to the teaching environment (classroom) with the aim of promoting meaningful learning, namely: Open Work; Quite; Motivation; Creativity; Concept Maps; and, Curricular Adaptation. Based on this identification and mobilized in search of alternatives that would lead students to construct meaningful learning, the study aims to discuss a didactic sequence supported by TAS and that contemplates the key variables announced by Ballester. With a guiding question, the study infers the following: what is the relevance of using the key variables announced by Ballester in the teaching-learning process of Electricity content in Elementary School? The objective is to structure, implement and evaluate a didactic sequence anchored in the TAS and the key variables proposed in the Ballester Method, for the study of electricity in the eighth year of Elementary School. These variables, based on a didactic structure supported by TAS, are part of the didactic sequence designed for the study of Electricity and are the object of investigation in the study, in order to analyze their contribution to meaningful learning. The structured didactic proposal is aligned with the National Common Curricular Base (BNCC) and was applied in 23 periods, in an eighth-year elementary school class at a state public school in the interior of Rondônia. The research assumes a qualitative approach and action research, involving the production of data based on records in the logbook of the researcher who is the class teacher; production of a conceptual map at the end of the meetings; and results of the summative assessment, especially in comparison with the initial prior knowledge questionnaire answered at the beginning of the sequence. The analysis categories established in the study are associated with signs of significant learning (relationship between the initial questionnaire and the summative assessment carried out at the end and the conceptual maps) and didactic feasibility brought especially by the perception of the teacher/researcher. As a result in the first category, the study points out that there have been advances in terms of knowledge, especially in the concepts of voltage and electrical power. Still in this category, the conceptual maps show that few students at this stage of first contact with this resource are able to fully elaborate, however, it shows that those who do are able to establish relationships, identify propositions and show the hierarchy of concepts. In the second category, the study highlights the didactic relevance of the five key variables announced by Ballester and brought into the didactic sequence, especially in terms of promoting spaces for sharing among colleagues, creativity, motivation and relationship with the environment. The educational product that accompanies the study refers to the didactic sequence designed with emphasis on the variables announced in the Ballester Method, as a way of providing support material for Science teachers who work in elementary education. The educational product is available on the Educapes Portal (http://educapes.capes.gov.br/handle/capes/739678), on the program page and on the PPGECM educational products page.